The prospective contribution of kesterites to next-generation technologies - Mohammad Istiaque Hossain (17944964) (2025)
Kesterite-based Cu₂ZnSn(S,Se)₄ (CZTSSe) thin films have emerged as versatile and sustainable materials for a wide spectrum of next-generation technologies, including solar photovoltaics, photodetectors, sensors, thermoelectric devices, photoelectrochemical water splitting, energy storage systems (such as lithium-ion batteries and supercapacitors), and even antibacterial treatments. In the realm of photovoltaics, CZTSSe thin-film solar cells have achieved a notable power conversion efficiency of 12.6 %. This review delves into both encapsulated and non-encapsulated device structures, examining their structural stability and degradation mechanisms over time. The key advantages of CZTSSe include their earth-abundant, non-toxic composition, tunable optoelectronic properties, and compatibility with low-cost, scalable fabrication techniques. Such material has favorable empirical properties at both the nano- and micro-level, such as a tunable direct bandgap (∼1.0–1.5 eV), high absorption coefficient (>10⁴ cm⁻¹), earth-abundant and non-toxic elemental composition, and potential for low thermal conductivity—traits that are especially beneficial for photovoltaic and thermoelectric applications. These features strongly align with global sustainability goals and the principles of a circular economy, particularly through reduced environmental impact and the potential for recycling. The review also addresses critical challenges related to stability, reproducibility, and ageing effects, providing insights into defect passive action, interface engineering, and compositional tuning to enhance long-term performance. Additionally, the potential of CZTSSe for material and energy storage is thoroughly explored, reinforcing the material’s promise beyond traditional photovoltaics. By presenting recent advancements, fabrication strategies, and emerging multifunctional applications, this review underscores the transformative potential of CZTSSe in shaping a sustainable technological future. Other Information Published in: Nano-Structures & Nano-Objects License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.nanoso.2025.101480